Pendampingan Digital Marketing dan Optimalisasi Penjualan Bagi Sektor UMKM Toko Besi Garuda Steel - Agum Panji Kusumo; Ratri Paramitalaksmi (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
MSMEs play an important role in the Indonesian economy, but barriers to digital adaptation often hinder their growth and competitiveness. This digital marketing mentoring program aims to optimize the sales of MSME Toko Besi Garuda Steel through branding and utilization of digital platforms. The initial stage includes in-depth interviews to understand the needs and challenges of MSMEs, followed by mentoring in creating a logo as a visual identity element that reflects business values. The next step is to help MSMEs create and manage Instagram accounts, focus on profile settings, and attractive content strategies. Education about digital platform features also provides insight for MSME owners in utilizing online marketing opportunities more effectively. This program not only helps MSME Toko Besi Garuda Steel build a digital presence, but also increases understanding of the importance of branding and communication strategies to increase consumer purchasing power. This mentoring is a strategic step to build a strong foundation for MSME Toko Besi Garuda Steel in facing competition in the digital era. With the implementation of the right strategy, Toko Besi Garuda Steel is expected to be able to increase productivity, competitiveness, and turnover sustainably. This program provides an implementation model that can be replicated to empower other MSMEs in similar sectors.